Old unreduced obturator dislocation of the hip: A case report - Li, Wen-Zhao (World J Clin Cases, 2021)
BACKGROUND: Obturator dislocation is a rare type of hip dislocation, accounting for about 2%-5% of all hip dislocations. The occurrence of old unreduced obturator dislocation is even more infrequent, with only 17 cases reported in nine studies, most of which were from the 1950s to 1980s in developing countries. CASE SUMMARY: A 38-year-old woman from Hunan Province, China presented with stiffness of the left hip in abduction, flexion, and external rotation after falling from a 2-meter-tall tree onto her left knee 1.5 mo prior. Pelvic radiograph and computed tomography revealed obturator dislocation of the left hip accompanied by impaction fracture at the superolateral aspect of the left femoral head without associated acetabulum fracture. Open reduction was performed, resulting in restoration of the concentric alignment of the left hip. After surgery, 6-wk skin traction was applied and the patient was kept in bed for an additional 2 wk. At 3 mo after surgery, the patient reported experiencing some pain, which did not affect the function of the affected limb, and some movement restriction but no abduction deformity or claudication was present. An X-ray showed that the left hip was homocentric, and there was no sign of posttraumatic arthritis or avascular necrosis. CONCLUSION: Open reduction may be an effective treatment strategy for the rare condition of old unreduced obturator dislocation with short neglect time.